2014
DOI: 10.1038/nmat3911
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature solution-processed wavelength-tunable perovskites for lasing

Abstract: Low-temperature solution-processed materials that show optical gain and can be embedded into a wide range of cavity resonators are attractive for the realization of on-chip coherent light sources. Organic semiconductors and colloidal quantum dots are considered the main candidates for this application. However, stumbling blocks in organic lasing include intrinsic losses from bimolecular annihilation and the conflicting requirements of high charge carrier mobility and large stimulated emission; whereas challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

84
2,715
7
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 2,900 publications
(2,844 citation statements)
references
References 29 publications
84
2,715
7
5
Order By: Relevance
“…We observed that band gaps calculated within DFT seem to increase as the symmetry of the unit cell decreases [9]; this effect is common to other hybrid perovskite systems [34], and has been experimentally confirmed for the orthorhombic to tetragonal phase transition in MAPbI 3 [55]. On the other hand, the band gaps are sensitive not only to the orientation of the MA molecules, but also to the size of the unit cell for a given crystal system.…”
Section: Electronic Band Gapssupporting
confidence: 66%
“…We observed that band gaps calculated within DFT seem to increase as the symmetry of the unit cell decreases [9]; this effect is common to other hybrid perovskite systems [34], and has been experimentally confirmed for the orthorhombic to tetragonal phase transition in MAPbI 3 [55]. On the other hand, the band gaps are sensitive not only to the orientation of the MA molecules, but also to the size of the unit cell for a given crystal system.…”
Section: Electronic Band Gapssupporting
confidence: 66%
“…Rapid advances in this young research field has led to spectral tunability from 400-800nm 122 and extremely large exciton diffusion length of around 1µm for polycrystalline thin films 123 . Organolead trihalide perovskite single crystals have been reported by implementing a novel antisolvent vapourassisted growth technique.…”
Section: Ideal Sensitizer Characteristicsmentioning
confidence: 99%
“…These excellent properties, along with their high quantum yield and wavelength tunability, make halide perovskites ideal for light‐emission applications such as for light‐emitting diodes (LEDs), light‐emitting field‐effect transistors, and lasing 13, 14, 15, 16, 17, 18, 19. Since the first demonstration of ultrastable amplified spontaneous emission (ASE) with broad spectral tunability from perovskite thin films and lasing from perovskite crystals,20 perovskite lasing in a broad range of cavity structures, including microplatelets,21 nanowires,22 microspheres,23 and distributed Bragg reflection (DBR) mirrors,24 have been realized 25. Notably, Zhu et al recently reported a solution‐processed technique to synthesize single‐crystal perovskite nanowires and demonstrated their application on lasers with high‐quality factor and low lasing threshold 26.…”
Section: Introductionmentioning
confidence: 99%